Emergence of 2, 3, 5-trisubstituted tetrahydrofuran natural products and their synthesis. Issue 36 (3rd September 2020) - Fernandes, Rodney A.; Gorve, Dnyaneshwar A.; Pathare, Ramdas S.
Abstract : Diverse syntheses of emerging 2, 3, 5-trisubstituted-THF natural products are reviewed encompassing strategies based on catalytic methods, cascade reactions and rearrangements. Abstract : The emergence of various 2, 3, 5-trisubstituted tetrahydrofuran natural products in the recent literature and their synthesis is the focus of this review. These molecules exhibit varied bioactivities and have garnered the interest of several synthetic chemists owing to their efficient synthesis. A few of them have been synthesized and their absolute stereo structure has been confirmed for the first time. These will be appealing candidates in future synthetic investigations along with the untouched molecules. Thus, this compilation will reveal these molecules for expansion of their diversity within the realm of both synthesis and bioactivity studies.